Comparison Of Lowland Rice Farming With Various Irrigation Sources In Manyak Payed District, Aceh Tamiang Regency - Nely Fadila; Retna Astuti; Harso Kardhinata (CV. AFDIFAL MAJU BERKAH, 2022)
The aim of this study was to analyze the comparative income of paddy rice farming from the irrigation source method used in Manyak Payed District, Aceh Tamiang Regency. The sample for this study was 87 respondents spread across 15 villages in the Manyak Payed sub-district, Aceh Tamiang district. As for the results of this study, lowland rice farmers in Manyak Payed District, Aceh Tamiang Regency who use technical irrigation sources earn greater income and are significantly different from the group of farmers with irrigation sources from rivers with 6 inch diameter pumps, with an average net profit of a net profit of IDR 39,685,778 for technical irrigation and 34,842,909 for 6-inch pump irrigation, and the lowest is 3-inch pump irrigation with a profit of IDR 33,307,444. not too big compared to the other 2 irrigation systems, plus the maintenance costs are higher than technical irrigation and 6 inches.